Analysis of the three-dimensional image characteristics of bone island in jaw using CBCT - YAN Shijie, YANG Lianfeng, WANG Jingyan, ZHANG Juan, ZHU Tingting, LENG Diya, ZHOU Guangchao, GU Peiyu (Editorial Office of Stomatology, 2024)
Objective To analyze three-dimensional(3D) radiographic characterizations of bone island(BI) in jaw using cone-beam computed tomography(CBCT). Methods CBCT data from four thousand patients were selected, reconstructed and analyzed using NNT 10.0 software. The sagittal, coronal and axial planes were used to analyze the 3D radiographic characteristics of BIs, including the localization, shape, density, boundary, the relationship between BIs and tooth and bone cortex, diameter and anatomical structures and complications involved. Their relationship with gender were analyzed. Results A total of 803 people had BIs, with the prevalence rate of 20.08%, including 338 males with 389 BIs and 465 females with 526 BIs. Both males and females had a dominant BI, and the ratio between male and female was 1∶1.38, but the difference was not statistically significant(P>0.05). The BIs of both male and female mostly occurred in the mandibular premolars and molars area, and appeared irregular in shape, dense and contact with lingual bone cortex. Mostly BIs were apical type and with unclear boundary. The mean maximum diameter of mesial/distal direction was greater than buccal/lingual direction(P<0.05). The most commonly involved anatomy structure was the inferior alveolar neural canal, cortical infiltration and mental foramen. Conclusion There are no significant differences between males and females in the three-dimensional image characteristics of BIs in Chinese populations. CBCT can accurately and comprehensively analyze the 3D radiographic characteristics of BI and its relationship with the surrounding teeth and bone.